Maintenance Electroconvulsive Therapy Is an Essential Medical Treatment for Patients With Catatonia: A COVID-19 Related Experience - Ghaziuddin, Neera; Yaqub, Tareq; Shamseddeen, Wael; Reddy, Priyanka; Reynard, Hannah; Maixner, Daniel (Frontiers in Psychiatry, 2021)
Aim: Describe naturalistic clinical course over 14 weeks in a mixed adolescent and a young-adult patient group diagnosed with developmental delays and catatonia, when the frequency of maintenance electroconvulsive therapy (M-ECT) was reduced secondary to 2020 COVID-19 pandemic restrictions. Methods: Participants were diagnosed with catatonia, and were receiving care in a specialized clinic. They (n = 9), F = 5, and M = 4, ranged in age from 16 to 21 years; ECT frequency was reduced at end of March 2020 due to institutional restrictions. Two parents/caregivers elected to discontinue ECT due to concern for COVID-19 transmission. Majority (n = 8) were developmentally delayed with some degree of intellectual disability (ID). Observable symptoms were rated on a three point scale during virtual visits. Results: All cases experienced clinically significant decline. Worsening of motor symptoms (agitation, aggression, slowness, repetitive self-injury, stereotypies, speech deficits) emerged within the first 3 weeks, persisted over the 14 week observation period and were more frequent than neurovegetative symptoms (appetite, incontinence, sleep). Four participants deteriorated requiring rehospitalization, and 2 among these 4 needed a gastrostomy feeding tube. Conclusion: Moderate and severe symptoms became apparent in all 9 cases during the observation period; medication adjustments were ineffective; resuming M-ECT at each participant's baseline schedule, usually by week 7, resulted in progressive improvement in some cases but the improvement was insufficient to prevent re-hospitalization in 4 cases. In summary, rapid deterioration was noted when M-ECT was acutely reduced in the setting of COVID-19 related restrictions.